2016
DOI: 10.1177/1357633x15610720
|View full text |Cite
|
Sign up to set email alerts
|

Availability, spatial accessibility, utilisation and the role of telehealth for multi-disciplinary paediatric cerebral palsy services in Queensland

Abstract: Traditional methods of delivering services to CP patients do not meet their needs. Clinicians have found telehealth is a feasible and satisfactory delivery method. However, the use of telehealth is still limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 22 publications
0
69
0
Order By: Relevance
“…Despite this research evidence, perceptions that teleahealth might not be as effective as face-to-face interventions remain (Edirippulige et al, 2016). As telehealth is a service delivery model, and not the intervention itself, the question should not be "Is telehealth effective", the same way we would not ask 'Is physical or occupational therapy effective'.…”
Section: Evidence For Use Of Telehealth For Children With Disabilitiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite this research evidence, perceptions that teleahealth might not be as effective as face-to-face interventions remain (Edirippulige et al, 2016). As telehealth is a service delivery model, and not the intervention itself, the question should not be "Is telehealth effective", the same way we would not ask 'Is physical or occupational therapy effective'.…”
Section: Evidence For Use Of Telehealth For Children With Disabilitiesmentioning
confidence: 97%
“…A review in 2013 concluded that sufficient evidence existed to justify the use of telehealth in pediatric occupational therapy (Zylstra, 2013). It is one of many that support the feasibility of using telehealth in physical and occupational therapy in pediatrics, and the perception that telehealth could help increase access to services (Edirippulige et al, 2016;Iacono et al, 2016). One of the limitations identified by Zylstra (2013) was that most studies primarily investigated families' and therapists' satisfaction, as opposed to children and family outcomes.…”
Section: Evidence For Use Of Telehealth For Children With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, telemedicine is not new. To date, telemedicine has been tried and even regularly used in a variety of clinical situations such as stroke evaluation [6], psychiatric care [7], newborn resuscitation [8], multidisciplinary care [9], There are many resources available to guide some aspects of a telemedicine visit, including the American Telemedicine Association "Operating Procedures for Pediatric Telehealth" [15], an overview on adult rehabilitation telemedicine visits [16], telemedicine for pediatric gastroenterologists [17], and a how-to for the adult telemedicine musculoskeletal exam [18]. While these resources can help a PRM provider with telerehabilitation medicine visits for certain diagnoses or clinical scenarios, these resources do not provide specific guidance for pediatric telerehabilitation medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of children travel for long distances to consult a specialist (average distance of 836 km), and clinicians perceived healthcare services as inadequate in terms of accessibility for children with these movement disorders. 41 Moreover, videoconferencing allows both parents to participate in clinic for better management.…”
Section: The Solutionmentioning
confidence: 99%